High-intensity focused ultrasound for the treatment of liver tumours. - Kennedy, J; Wu, F; ter Haar, G; Gleeson, F; Phillips, R; Middleton, MR; Cranston, D (2004)
High-intensity focused ultrasound (HIFU) has been investigated as a tool for the treatment of cancer for many decades, but is only now beginning to emerge as a potential alternative to conventional therapies. In recent years, clinical trials have evaluated the clinical efficacy of a number of devices worldwide. In Oxford, UK, we have been using the JC HIFU system (HAIFU Technology Company, Chongqing, PR China) in clinical trials since November 2002. This is the first report of its clinical use outside mainland China. The device is non-invasive, and employs an extracorporeal transducer operating at 0.8-1.6 MHz (aperture 12-15 cm, focal length 9-15 cm), operating clinically at Isp (free field) of 5-15 KWcm(-2). The aims of the trials are to evaluate the safety and performance of the device. Performance is being evaluated through two parallel protocols. One employs radiological assessment of response with the use of follow-up magnetic resonance imaging and microbubble-contrast ultrasound. In the other, histological assessment will be made following elective surgical resection of the HIFU treated tumours. Eleven patients with liver tumours have been treated with HIFU to date. Adverse events include transient pain and minor skin burns. Observed response from the various assessment modalities is discussed.